Classification Of Category Selection Title Undergraduate Thesis Using K-Nearest Neighbor Method - Ratih Kumalasari Niswatin; Ardi Sanjaya (Institute of Advanced Engineering and Science, 2017)
This research makes the classification system of category selection title undergraduate thesis titleuse k-nearest neighbor method. This research will be conducted on the students of Informatics Engineering Department Faculty of Engineering, Universitas Nusantara PGRI Kediri. The purpose of making this system is to employee department and students to more easily make a classification of category selection undergraduate thesis title based on the field of interest and field of expertise of each student. The method used to classify the selection of undergaduate thesis title categories is k-nearest neighbormethod using several criteria based on students' interests and expertise in a particular field or course. The result of this sitem is an information category of undergraduate thesis title of students who have been processed based on the field of interest and field of expertise of each student.